Disparity of Risk Factors Stunting on Toddlers in the Coast and the Mountain Areas of Sinjai, South Sulawesi (Public Health Perspective Journal, 2019)
Stunting is a form of malnutrition is characterized by short stature in children. The prevalence of toddler stunting in 2017 in South Sulawesi is 34%, while in  Sinjai Regency in 2016 is 34.6%, 2017 is 43.7%, and 2018 is 35.8%. The purpose of this study was to analyze the disparity of stunting risk factors in toddlers on the coast and mountain areas. This study used a case-control design. The sampling techniques are Fixed Disease Sampling and Stratified Proportional Random Sampling. The population consists of the entire toddler in Sinjai, whereas consists of 60 toddler stunting age 9-59 months and 60 normal toddler on the coast and mountain areas. The instrument used the Food Frequency Questionnaire (FFQ) sheet. The data were analyzed by univariate bivariate, Chi Square and multivariate with logistic regression. The Chi square test results showed that the risk factors stunting on the coast is energy intake (p = 0.03; OR = 2.99) and Fe (p = 0.03; OR = 2.99), while in the mountain is the protein intake (p = 0.01; OR = 6.5), Fe (p = 0.01; OR = 4) and Zn (p = 0.00; OR = 5.4). The logistic regression results indicate that stunting dominant risk factors in the coast area is the intake of proteins and in the mountain area is the intake of Fe. There is a disparity between the risk factors of stunting toddler in the coast  and mountain area. Poor nutritional intake increases the risk of stunting so it is necesary to increase the consumption of food sources of nutrients for toddlers.Stunting merupakan bentuk dari kurang gizi. Tahun 2017, stunting di Provinsi Sulawesi Selatan masih tinggi (34%) dan Kabupaten Sinjai tahun 2016 (34,6%), 2017 (43,7%), dan 2018 (35,8%). Tujuan penelitian untuk menganalisis disparitas faktor risiko stunting balita di wilayah pesisir pantai dan pegunungan. Penelitian ini merupakan penelitian kuantitatif menggunakan desain case control. Teknik sampling yaitu Fixed Desease Sampling dan Stratified  Proportional Random Sampling. Populasi adalah seluruh balita di Sinjai dan sampel yaitu balita stunting usia 9-59 bulan dan minimal sampel sebanyak 60 balita stunting di wilayah  pesisir pantai dan pegunungan serta 60 balita normal di wilayah pesisir pantai dan pegunungan. Instrumen menggunakan lembar FFQ Semikuantitatif. Data dianalisis univariat, bivariat dengan uji Chi Square dan  multivariat dengan regresi logistik. Hasil uji Chi Square menunjukkan faktor risiko stunting di wilayah pesisir pantai yaitu asupan energi dengan nilai p=0.03 OR=2.99 dan Fe dengan nilai p=0.03 OR=2.99 sedangkan di pegunungan yaitu asupan protein dengan nilai p=0.01 OR 6.5, Fe dengan nilai p=0.01 OR=4, dan Zn dengan nilai p=0.00 OR=5.4. Hasil regresi logistik menunjukkan faktor risiko stunting yang dominan di wilayah pesisir pantai yaitu asupan protein dan di wilayah pegunungan yaitu asupan Fe. Terdapat disparitas faktor risiko stunting pada balita antara wilayah pesisir pantai dan pegunungan.